OC-042 Sensitivity Of Annual Faecal Immunochemical Tests For Haemoglobin (fit) For Detecting Advanced Neoplasia In Patients Undergoing Three-yearly Surveillance Colonoscopy – The Fit For Follow-up Study. (9th June 2014) - MacRae, E; Brenner, A; Martin, J; Pearson, S; Piggott, C; Bowyer, H; Vart, G; von Wagner, C; Wardle, J; Halloran, S; Atkin, W
Abstract : Introduction: With increasing demand for colonoscopy in the NHS Bowel Cancer Screening Programme (BCSP) in England, there is a need for effective non-colonoscopic approaches to surveillance. We have undertaken a study to compare the sensitivity and specificity of a faecal immunochemical test for haemoglobin (FIT) annually for three years with colonoscopy surveillance, in patients diagnosed with intermediate-risk adenomas following a positive faecal occult blood test in the BCSP. Methods: Participants are invited to complete a FIT (OC-SENSOR, Eiken Chemical Co. Ltd.) annually while awaiting their first surveillance colonoscopy. Those testing positive (>40 µg Hb/g faeces) are invited to have their three-year colonoscopy brought forward, while those testing negative are sent another FIT a year later until they have completed three rounds of testing. We aim to determine the sensitivity of FIT in detecting colorectal cancer or advanced adenomas (≥10 mm, or with tubulovillous or villous histology, or with high-grade dysplasia), using colonoscopy as the reference standard. Results: We invited 8009 people to participate in the study, of whom 5840 (72.9%) consented. The positivity rate in Round 1 was 5.8% (336/5840). To date, 265/303 (87.5%) have had an early colonoscopy: 62/265 (23.4%) had advanced adenomas and five (1.9%) had cancer. 33/336 (9.8%) declined an early colonoscopy. To date, in Round 2 we have invited 2800 patients who tested FIT negative in Round 1: 2560 (91.4%) completed a second FIT and 115/2560 (4.5%) tested positive. 85/106 (80.2%) have received an early colonoscopy: 13/85 (15.3%) had advanced adenomas and two (2.4%) had cancer. 9/115 (7.8%) declined an early colonoscopy. A total of 2445 participants had negative FIT tests in Rounds 1 and 2 and will be invited to complete a final FIT, prior to their surveillance colonoscopy. Satisfaction with the study was high among those who completed a questionnaire, with 95.4% (4177/4378) of FIT-negative and 91% (203/223) of FIT-positive participants in Round 1 stating that they would complete another kit in future. Conclusion: Compliance with the study was high, and the majority of participants reported that they would use FIT again. Almost a quarter (23.4%) of patients in Round 1 who had an early colonoscopy had advanced adenomas, falling to 15.3% in Round 2. Round 2 is ongoing, with Round 3 starting in January 2014. Disclosure of Interest: None Declared.